Intelecto geral e polarização do conhecimento na era da informação: o Vale do Silício como exemplo - Rodrigo Moreno Marques (2014)
Two questions stimulated the research. Firstly, we ask how the Political Economy of Information and Knowledge and Karl Marxs thoughts can illuminate the discussion of the role of information and knowledge in the current socioeconomic dynamics. We also ask which similarities and differences can be found when these theoretical constructs are confronted with the point of view of the information age workers. As the general objective of the investigation, we aim to compare the theories of the Political Economy of Information and Knowledge with the perceptions of the information age workers, concerning the role of information and knowledge in the contemporary socioeconomic dynamics. The Silicon Valley, located at California, United States, known as the cradle of great scientific and technological advances, as well as an innovative place, was chosen for an empirical research. Semi structured interviews were conducted with representatives of the local workers. The discourse analysis was adopted as an analytical instrument and the dialectics as a guide to our point of view. To expose the main aspects of the registered discourses, the arguments of the respondents were separated into four themes: economy, education, labor and intellectual property. Rather than expose positive achievements for the society, the respondents claim that the Silicon Valley economic model increases the unemployment and the underemployment at the region, exacerbates the local socioeconomic inequalities and stimulates problems at the countries that attract the outsourced industrial production. The Silicon Valley educational system, pictured as unequal and exclusionary, is considered a determinant factor of the way each individual participates in the labor market of the information age. The discourses indicate that the so called knowledge labor, intellectual labor or cognitive labor is available to a small minority of the locals. The emancipatory promises of the virtual work, born with the information and communication technologies, are overshadowed by adversities and barriers in the realm of real work. About intellectual property rights, the respondents criticize the US patent system and emphasize its social costs. Unveiling the contradictions of the local reality, the Silicon Valley voices deconstruct the imaginary about the region disseminated by the common sense. Faced by such discrepancy between the idealized image of this cluster and the real discourse of those who are parts of it, we can argue that there is an ongoing polarization of knowledge in the investigated universe. The general intellect departs from its original promise of universality.